Minat Beli Produk Fashion: Penggunaan Hashtag Dan Review Produk Pada Aplikasi TikTok - Fahimah, Mar'atul; Ainiyah, Isyam Rotul (Jurnal Ecoment Global, 2023)
The trend of tiktok poisoning has resulted in consumptive behavior towards Gen Z.. This can be seen in theaii_collection account in utilizing social media through the tiktok application by making product reviews using thehashtag #racuntiktok which attracts consumer interest thereby increasing interest in buying fashion products ataii_colection. This study aims to examine and analyze the factors that influence the intention to buy fashion productsat aii_collection. Sampling was taken using a purposive sampling technique, which was only taken for those whowatched the video review with the hashtag #racuntiktok, with a quantitative approach. The data analysis techniqueused was validity, reliability, multiple linear regression analysis, classical assumption test, hypothesis testing (t testand f test), and R determination. The results of testing the variable use of hashtags (X1) partially has a positive effectbecause t count < t table (2.898 < 1.984) so that it has a significant effect on interest in buying fashion products.While the results of testing the product review variable (X2) have a positive and significant with t count < t table(5.097 < 1.984) so that it influences the intention to buy fashion products.